Steam Treatment of Wood in Close System - Fdili Alaoui, B.; Zeriouh, A.; Belkbir, L. (Asian Journal of Chemistry, 2010)
The present work consists to determine the reactivity of argania wood after its steam treatment at the temperature TT in autoclave. The thermogravimetric study in dynamic pyrolysis mode under TT (TT = 153; 169; 200; 236 and 250°C) and R (R = 3; 6; 9 and 12) indicates that the wood present the same type of losses before and after treatment with various intensities. Consequently the light organic materials the quantity of hemicellulose and lignin in this wood are modified by this treatment while the cellulose remains practically intact. Furthermore the observed modifications are due to the action of the saturating water pressure, and not to the applied temperature. The tratment with steam in closed system could be used to modify the composition of argan wood essentially for hemicellulose and lignin constituents.